Common care practices among effective community-based specialist palliative care teams: a qualitative study - Seow, Hsien (BMJ Support Palliat Care, 2020)
OBJECTIVE: Evidence has shown that, despite wide variation in models of care, community-based specialist palliative care teams can improve outcomes and reduce acute care use at end of life. The goal of this study was to explore similarities in care practices among effective and diverse specialist teams to inform the development of other community-based teams. METHODS: Interviews with 78 providers and administrators from 11 distinct community-based specialist palliative care teams from Ontario, Canada were conducted. Interviews were audio-recorded, transcribed and analysed using an inductive approach to identify common themes. RESULTS: 3 key themes across all teams emerged. First, the distinct models of care were generally summarised into 3 models: primary care and specialist providers either collaborated by transferring, sharing or consulting in care. Second, teams explicitly or implicitly followed 7 common care practices related to: specialised expertise 24/7; intrateam communication; timeliness; physical symptom and psychosocial–spiritual management; education; peace and fulfilment; and advocacy for patient preferences. Third, all teams emphasised the importance of team building, even more than using clinical tools and processes. CONCLUSIONS: Despite wide variation in models of care among community-based specialist palliative care teams, this large qualitative study identified several common themes in care practices that can guide the development of other teams.